HUMAN FACE RECOGNITION USING IMAGE PROCESSING PCA AND NEURAL NETWORK - Yogesh B. Sanap; Dr. Anilkumar N. Holambe (International Journal of Innovations in Engineering Research and Technology, 2021)
Security and authentication of a person is a vital part of any business. There are many techniques used for this purpose. One of technique is human face recognition. Human Face recognition is an effective means of authenticating a person. The benefit of this approach is that, it enables us to detect changes in the face pattern of an individual to substantial extent. The recognition system can tolerate local variations in the face expression of an individual. Hence Human face recognition can be used as a key factor in crime detection mainly to identify criminals. There are several approaches to Human face recognition of which Image Processing Principal Component Analysis (PCA) and Neural Networks have been included in our project. The system consists of a database of a set of facial patterns for each individual.